A relação entre os gastos públicos e o crescimento econômico: uma análise para os municípios paraibanos no período 2000-2008 - Silva, Laércio Damiane Cerqueira da (2012)
This paper aims to explain the theme of public spending and its relationship with economic growth, bringing a literature review national, international and an analysis of the influence of certain expenditures by function on economic growth in municipalities from Paraiba. Such expenses would be with: Assistance and Social Welfare, Health and Sanitation, Education and Culture, Public Safety, Housing and Urban Development, Legislative, Administration and Planning. For this analysis, we used panel data from a sample of 212 of the 223 municipalities from Paraíba between 2000 and 2008, a dynamic approach by Generalized Method of Moments-System (System-GMM) proposed by Arellano and Bond (1991), Arellano and Bover (1995) and developed by Blundell and Bond (1998). And as a theoretical model, we adopted an extension of the production function of Barro (1990). The proxy for the stock of physical capital is the consumption of electricity for industrial and commercial city of Paraiba, whereas the stock of human capital was created by counting the number of people with eight years of study, plus the flow of conclusive primary education by municipality and also the number of people aged 12 or more of study, along with the flow conclusive school each year by the municipality from Paraíba. To achieve the proposed objective, the study tried to find out what is the relationship between public spending and economic growth of municipalities from Paraíba. Overall, the results corroborate the literature, the point at which government spending influence the product formation and public investment in physical capital and human capital can raise the productivity of the economy. The results show that only the capital human measured by elementary school, was also relevant for the growth of municipalities from Paraíba and the impact is greater than this physical capital. Spending on Public Safety, Welfare and Pension Plan, Planning and Administration and bear no relation to the product. Legislative expenses had the highest elasticity product, while spending on Education and Culture, Health and Sanitation, and Housing and Urban Development have low elasticity products, thus influencing modest economic growth.